Institutions, networks and entrepreneurship development in Russia: an exploration - Ruta Aidis; Saul Estrin (Institute for the Study of Labor (IZA), 2006)
In this paper we explore the ways in which institutions and networks influence entrepreneurial development in Russia. By utilizing new Global Entrepreneurship Monitor (GEM) data collected in 2001, we investigate the effects of the weak institutional environment in Russia in terms of three dimensions: on the rate of productive entrepreneurial activity measured in terms of start-ups and existing business owners; on the characteristics of business owners; and on business financing. In addition, the analysis explores the effectiveness of Russia's informal networks for circumventing the weak institutional environment for business development. Our results indicate that Russia's business owners share many of the same characteristics as business owners in advanced western countries, though education is not associated with entrepreneurial activity. However, the main differences are in the sources of financing and the fact that relatively few individuals engage in productive entrepreneurial activity. Our results support the notion of the limited effectiveness of Russia's networks for supporting entrepreneurial activity in its weak institutional environment.
Keywords: J23; M13; 330; entrepreneurship; institutions; networks; Russia; Unternehmer; Institutionalismus; Netzwerk; Unternehmensgründung; Russland